Plant phosphorus-acquisition and -use strategies affect soil carbon cycling - Ding, Wenli; Cong, Wen-Feng; Lambers, Hans (Trends in ecology & evolution (Amsterdam), 2021)
Increased anthropogenic nitrogen (N) deposition is driving N-limited ecosystems towards phosphorus (P) limitation. Plants have evolved strategies to respond to P limitation which affect N cycling in plant‐soil systems. A comprehensive understanding of how plants with efficient P‐acquisition or ‐use strategies influence carbon (C) and N cycling remains elusive. We highlight how P‐acquisition/-use strategies, particularly the release of carboxylates into the rhizosphere, accelerate soil organic matter (SOM) decomposition and soil N mineralisation by destabilising aggregates and organic‐mineral associations. We advocate studying the effects of P-acquisition/-use strategies on SOM formation, directly or through microbial turnover. In response to low P availability, plants have evolved a variety of P‐acquisition/‐use strategies. These may affect N cycling by influencing SOM turnover.Two microbial strategies (N-mining and co-metabolism) have been proposed to explain microbially mediated priming effects. We suggest that priming should be explained from the perspective of the capacity of a plant to acquire or utilise P under low-P conditions.Efficient P‐acquisition/-use strategies may change N cycling by affecting SOM decomposition. For example, a highly efficient P-mobilising strategy, carboxylate release, may destabilise aggregates and organic‐mineral associations through chelation of metals (such as Fe, Al) and then accelerate SOM decomposition; flavonoids may work in a similar way.Efficient P‐acquisition/-use strategies may affect SOM formation directly or indirectly through microbial turnover.